Pengendalian Persediaan Bahan Baku Pembuatan Roti Menggunakan Metode Economic Order Quantity Pada Top’s Bakery Situbondo - Nailah Altoffina (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze raw material inventory control at Top’s Bakery Situbondo using the Economic Order Quantity (EOQ) method. Unstable inventory levels can lead to cost inefficiencies, either due to excess stock or shortages during the production process. This research employs a descriptive quantitative approach, with data collected through direct interviews with the shop owner and documentation of production processes and inventory management. The results indicate that the EOQ method can optimize purchase quantities and significantly reduce total inventory costs. For wheat flour, the conventional method results in a purchase of 6,425 kg across 30 orders with a total cost of IDR 240,969, while the EOQ method recommends 6,710 kg in just 5 orders at a cost of IDR 62,600. For sugar, the conventional purchase is 2,850 kg in 30 orders costing IDR 194,986, whereas the EOQ method suggests 2,944.8 kg in 4 orders at a cost of IDR 46,454. EOQ also assists in accurately determining safety stock and reorder points. Thus, the application of the EOQ method proves to be more efficient and effective in controlling raw material inventory at Top’s Bakery.
Reupload file repository 10 Maret 2026_Ratna
Keywords: inventory; inventory control; inventory cost; Economic Order Quantity